A questionnaire based survey on knowledge, attitude and practices of medical practitioners regarding the prescribing of medications during pregnancy - Banu, Gausia; A. K., Afzal Khan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Prescribing during pregnancy requires careful estimation of risk/benefit ratio for the mother and her baby. Both, underestimation and overestimation can produce undesirable maternal and fetal outcomes hence the present study was undertaken to assess the knowledge, attitude and practices (KAP) of medical practitioners related to the prescribing of medications during pregnancy. Methods: A preformed structured questionnaire was administered to 41 medical practitioners. Multiple choice questions (MCQs) and yes/no type questions were used to assess their knowledge. Likert type questions studied their attitude and practices. Their perception of teratogenic risk of medications was evaluated using a visual analogue scale. The data so obtained was analyzed using descriptive statistics. Results: Completed questionnaires were returned by 76% of the survey participants. Among whom only 24% felt highly confident while others were less confident or unsure regarding their prescribing ability during pregnancy. 90% of the respondents reported that a disease should not be untreated or undertreated due to fear of teratogenicity. 81% exhibited good knowledge of the FDA pregnancy categorization of drugs and more than 80% were aware of the teratogenic risk associated with valproic acid, lithium, isotretinoin, warfarin & thalidomide. The perceived risk of teratogenicity (mean) suggested for them was 33, 52, 52, 43 & 62 percentage respectively. Conclusions: Most respondents exhibited a healthy attitude and a fairly sound knowledge, except for their perception of risk associated with individual drugs which was much higher than what is mentioned in the literature. Educational interventions may help to increase the awareness leading to better and confident prescribing.